"The Time of the Most Polar Bears": A Co-management Conflict in Nunavut - Dowsley, Martha; Wenzel, George (ARCTIC, 2009)
Since the 1990s, Inuit traditional knowledge (Inuit Qaujimajatuqangit) has taken on a substantial role in polar bear management in the Canadian territory of Nunavut through its direct use in quota-setting procedures. A co-management conflict has arisen from an increase of hunting quotas in January 2005 for Inuit living in the Baffin Bay and Western Hudson Bay polar bear population areas. The quotas were based on Inuit observations and their conclusion that these polar bear populations had increased. Scientific information suggests that climate change has concentrated polar bears in areas where humans are more likely to encounter them, but that the populations are in decline as a result of overhunting and climate-change effects on demographic rates. During consultations with wildlife managers and through other interviews in 2005, Inuit indicated their lack of support for quota reductions. Discussions with Inuit reveal two categories of problems that, though couched in the polar bear management issue, involve the co-management system and the integration of Inuit and scientific knowledge more generally. The first relates to direct observations of the environment by both Inuit and scientists and the synthesis of such information. The second relates to Inuit conceptualizations of human-animal relationships and the incorporation of scientific studies and management into that relationship. These problems reveal that differences between Inuit Qaujimajatuqangit and scientific knowledge are not fully understood and accounted for within the co-management system and that the system does not effectively integrate Inuit cultural views into management. Depuis les années 1990, les connaissances traditionnelles des Inuits (Inuit Qaujimajatuqangit) jouent un grand rôle dans la gestion des ours polaires du territoire canadien du Nunavut et ce, grâce au recours direct aux quotas. Un conflit de co-gestion s’est déclaré en raison de l’augmentation des quotas de chasse en janvier 2005 chez les Inuits vivant dans les régions peuplées ...